(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Objective: This study aimed to investigate the effects of Magnesium sulfate (MgSO4) iontophoresis on electrical activity and functional ability (step length of the affected side) of the gastrocnemius muscle Methods: A total of 50 patients aged 45_65 years of both genders who were diagnosed with chronic cerebrovascular accident (29 females and 21 males) were recruited in this study and randomly assigned into 2 equal groups. Subjects in Group A received MgSO4 iontophoresis in addition to passive stretching of the gastrocnemius for two session per week for 4 weeks, whereas group B underwent calf, quadriceps and hamstring muscle stretching for two sessions per week for 4 weeks. Electromyography was used to measure the electrical activity of the gastrocnemius muscle during rest and activity times (active plantar flexion) whereas the Biodex Gait Trainer 2 was used to measure the step length of the affected side; thus, patients were evaluated twice before and after allocation to each group. Results: Statistical analysis showed a significant change within all study variables when comparing pretreatment with posttreatment values in group A (p < 0.05) but not in group B (p > 0.05). Between-group analysis showed no significant changes in pretreatment values of all variables as (p > 0.05), whereas a significant change in all variables was observed in posttreatment values (p < 0.05). Conclusion: MgSO4 iontophoresis is more effective than traditional therapy (stretching) in managing the spasticity of poststroke patients.